2021
DOI: 10.1039/d1cy00178g
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of C–H bond activation by O2 on negatively charged Au clusters: α,β-dehydrogenation of 1-methyl-4-piperidone by supported Au catalysts

Abstract: Au nanoparticles supported on manganese oxide octahedral molecular sieve (OMS-2) can efficiently catalyze α,β-dehydrogenation of β-N-substituted saturated ketones using O2 as the terminal oxidant. However, despite the utility of this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…With reference to general understandings that O 2 can be reductively activated on anionic Au surface, [12–17] four possible reaction pathways were proposed toward this catalysis based on our previous studies (Figures S14 and S15) [36, 37] . The activation of O 2 in the presence of anionic Au nanoparticles was found to be important in all possible reaction pathways, considerably facilitating the oxidative dehydrogenation of piperidone derivatives.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…With reference to general understandings that O 2 can be reductively activated on anionic Au surface, [12–17] four possible reaction pathways were proposed toward this catalysis based on our previous studies (Figures S14 and S15) [36, 37] . The activation of O 2 in the presence of anionic Au nanoparticles was found to be important in all possible reaction pathways, considerably facilitating the oxidative dehydrogenation of piperidone derivatives.…”
Section: Resultsmentioning
confidence: 97%
“…Toward synthesis of enaminones, versatile synthetic intermediates for various organic compounds including heterocyclic compounds and natural products, [46] we had developed an efficient aerobic oxidative dehydrogenation of piperidone derivatives using supported Au nanoparticle catalysts [36] . Our further theoretical calculation revealed that, like some other aerobic oxidation reactions, [11–17, 47, 48] efficient activation of O 2 on negatively‐charged Au surface led to an excellent activity [37] . Therefore, we focused on this catalysis as a model reaction in order to evaluate the as‐proven supported anionic Au nanoparticle catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…M06 is an exchange–correlation functional often used in systems with transition metals especially Au, 38 , 48 , 49 and SDD is a basis set often used in systems with Au or Pd. 38 , 50 , 51 The solvent effect was calculated with a conductor-like polarizable continuum model using toluene. The transition state structures contained one imaginary frequency exhibiting atom displacements along the expected reaction pathway.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Our previous work on the Au-catalyzed α,β-dehydrogenation of 1-methyl-4-piperidone was computationally expensive because our use of various Au cluster models forced us to consider many adsorption sites for O 2 to cleave C–H bonds. 38 Also, oversimplifying the model of supported nanoparticle catalysts may result in conclusions that are inconsistent with reality. To elucidate the mechanism and establish a design strategy for heterogeneous catalysts, an established active site structure-catalyzed important elementary reaction such as C–H bond activation needs to be considered based on multiple aspects combined with experimental and theoretical approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation